Analysis Of Economic Status With Scientific Contraception Selections In Bpm Mogita Tlanakan Pamekasan - Nova Purmahardini Purma Hardini (Universitas Nahdlatul Ulama Surabaya, 2020)
Abstract    In the effort of decreasing the rate of population, government, implement the family plan program in order to make the quality family in year 2018. Many use injection hormonal contraception since it has the effective work, practice, cheap and safe relatively. In selecting the contraception effected by several factors, for instance age, education, work, parity, knowledge, resident, economic status, decision in the household, and culture. Economic status can influence someone in choosing the contraception particularly injection contraceptive.    The purpose of this search is to know the relationship between economic status and injection contraception selecting.    Research design is using analytic with cross sectional. This research was conducted at BPM Mogita Tlanakan Pamekasan starting from July 01, 2018  to August 31, 20018. Population is all the family plan acceptor and sample taking was done by probability sampling with sampling random simple with sample size is 49 respondents.    The research result denoted that from 49 respondents, 10 of then have the high economic statuses who are wearing injection are 3 persons and not are 7 persons. 14 respondents have the mid-economic status are wearing injection us 11 person and not is 3 persons and 25 respondent have the low economic status are wearing injection is 23 person and are not is 2 persons.    By using the Mann Whitney statistic with level of significant is 0,05 was obtained count  ≤  thus H0 was rejected, meaning that there is difference economic status with selecting the injection contraception and non-injection at di BPM Mogita Tlanakan Pamekasan.    Of the result research can be drawn the conclusion that economic status constitutes factor that influence the injection family plan selecting. In which they have the low economic status tend to choose the injection family plan than the high one. However, it needs the further research with seeing and enter the other factors that influence in contraception selecting. Keywords: economic status, injection contraception selecting.